2023
DOI: 10.3390/fishes8060319
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review of the Impacts of Climate Change on Salmon: Strengths and Weaknesses of the Literature by Life Stage

Abstract: As we confront novel environmental challenges, a full understanding of the physical and biological processes that govern species responses to climate change will help maintain biodiversity and support conservation measures that are more robust to irreducible uncertainty. However, climate impacts are so complex, and the literature on salmon and trout is so vast that researchers and decision makers scramble to make sense of it all. Therefore, we conducted a systematic literature review of climate impacts on salm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 456 publications
0
0
0
Order By: Relevance
“…Thiamine (vitamin B1) deficiency in fatty predatory fish results from an unbalanced diet abundant in fatty marine prey fish and thereby an excessive dietary intake of n−3 polyunsaturated fatty acids (n−3 PUFAs) [1,2]. It has affected salmonine species and lamprey (Lampetra fluviatilis) [2][3][4][5] and is called the M74 syndrome in the Baltic region [1][2][3]6] and Thiamine Deficiency Complex (TDC) in North America [7]. M74 has impaired the reproduction of Atlantic salmon (Salmo salar) feeding in the Baltic Sea (hereafter Baltic salmon or salmon), especially in the 1990s, but also after [8].…”
Section: Introductionmentioning
confidence: 99%
“…Thiamine (vitamin B1) deficiency in fatty predatory fish results from an unbalanced diet abundant in fatty marine prey fish and thereby an excessive dietary intake of n−3 polyunsaturated fatty acids (n−3 PUFAs) [1,2]. It has affected salmonine species and lamprey (Lampetra fluviatilis) [2][3][4][5] and is called the M74 syndrome in the Baltic region [1][2][3]6] and Thiamine Deficiency Complex (TDC) in North America [7]. M74 has impaired the reproduction of Atlantic salmon (Salmo salar) feeding in the Baltic Sea (hereafter Baltic salmon or salmon), especially in the 1990s, but also after [8].…”
Section: Introductionmentioning
confidence: 99%
“…Development of adaptive management plans to address climate-change impacts on fish, fisheries, aquaculture, and associated habitats and ecosystems requires knowledge of "local and context-specific indicators associated with climate stressors" (FAO, 2022). A comprehensive review of literature (meta-analysis across sub-disciplines) addressed strengths and weaknesses of climate-change research by life stage and showed the complexity of whole life-cycle approaches to adaptive management strategies for anadromous salmonids (Crozier & Siegel, 2023). Here, we investigated associations between marine survival (adult returns) of Japanese hatchery chum salmon at each life stage and a suite of hypothesized climate-change indicators.…”
Section: Introductionmentioning
confidence: 99%
“…In the last paper of this volume, Crozier and Siegel [19] performed a systematic literature review of climate impacts on Pacific and Atlantic salmon as a resource for stakeholders, managers, and researchers. They review published studies that address climate impacts on salmon from 2010 to 2021.…”
mentioning
confidence: 99%